HIPEREMESIS GRAVIDARUM PADA IBU HAMIL DI KLINIK BIDAN SUPRIYATI SRIBIT BERBAH SLEMAN - Pramukti Dian Setianingrum; Farah Irmania Tsani (STIKes Surya Global Yogyakarta, 2019)
Backgroud: The World Health Organization (WHO) explained that the number of Hyperemesis Gravidarum cases reached 12.5% of the total number of pregnancies in the world and the results of the Demographic Survey conducted in 2007, stated that 26% of women with live births experienced complications. The results of the observations conducted at the Midwife Supriyati Clinic found that pregnant women with hyperemesis gravidarum, with a comparison of 10 pregnant women who examined their contents there were about 4 pregnant women who complained of excessive nausea and vomiting. Objective: to determine the hyperemesis Gravidarum of pregnant mother in clinic. Methods: This study used Qualitative research methods by using a case study approach (Case Study.) Result: The description of excessive nausea of vomiting in women with Hipermemsis Gravidarum is continuous nausea and vomiting more than 10 times in one day, no appetite or vomiting when fed, the body feels weak, blood pressure decreases until the body weight decreases and interferes with daily activities days The factors that influence the occurrence of Hyperemesis Gravidarum are Hormonal, Diet, Unwanted Pregnancy, and psychology, primigravida does not affect the occurrence of Hyperemesis Gravidarum. Conclusion: Mothers who experience Hyperemesis Gravidarum feel nausea vomiting continuously more than 10 times in one day, no appetite or vomiting when fed, the body feels weak, blood pressure decreases until the weight decreases and interferes with daily activities, it is because there are several factors, namely, hormonal actors, diet, unwanted pregnancy, and psychology.